PERSECUTION IN FLORIDA: A MEMORY AND TRAUMA READING OF COLSON WHITEHEAD’S THE NICKEL BOYS - Maruthupandian, P.; Ajith, R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The abolition of slavery didn’t put an end to the problems of African Americans. They were reduced to people with no means of living. They couldn’t find a sure footing in such a vast country. They were dragged in to debt labour through various laws. Jim Crow being the popular that Nazis modeled their Anti Jew laws based on this. The Nickel Boys is a coming-of-age tale set in the Jim Crow era Florida that tells the story of Elwood who was caught in the web of the oppressive law and suffered infinitely. A tale with pain, torture, agony and hope through justice in the end.